Openness and Entrepreneurial Performance During COVID-19 Pandemic: Strategic Decision Comprehensiveness as an Inconsistent Mediator - Mu, Weiqi; Xu, Jie; Li, Fugui; Li, Siying; Li, Xue; Zhou, Mingjie (Frontiers in Psychology, 2022)
The COVID-19 pandemic severely hit small and micro-businesses. In the face of the impact of the pandemic, how to help entrepreneurs, especially small- and micro-businesses that are more sensitive to the impact of the epidemic, make decisions to reduce losses has become an issue worth paying attention to. From the perspective of personality approach, this article studied openness, which is the strongest predictor of entrepreneurial performance among the big five personality traits, and explored the impact of entrepreneurs' openness on entrepreneurial performance during the COVID-19 pandemic, as well as the inconsistent mediating role of strategic decision comprehensiveness on entrepreneurial performance. An online questionnaire survey was conducted among 238 entrepreneurs of small- and micro-businesses when China was recovering from the pandemic and starting to resume work and production (February 18 - February 26, 2020). Entrepreneurial performance during the COVID-19 pandemic was measured by comparing the business conditions before and after the pandemic. The results showed that entrepreneurs' openness positively impacted strategic decision comprehensiveness and entrepreneurial performance during the COVID-19 pandemic. Among the two competing hypotheses proposed by summarizing previous research, the results supported that strategic decision comprehensiveness negatively affected entrepreneurial performance. It indicated that entrepreneurs who tend to collect and analyze information extensively and then make decisions during the pandemic could not seize opportunities and improve their entrepreneurial performance. The results further supported that strategic decision comprehensiveness was an inconsistent mediator between openness and entrepreneurial performance, showing that entrepreneurs with low openness can also reduce the loss of entrepreneurial performance during the pandemic by making incomplete but rapid strategic decisions. This study found that the openness of entrepreneurs had a positive impact on strategic decision comprehensiveness for the first time and provided more empirical evidence for the negative impact of strategic decision comprehensiveness on entrepreneurial performance in the context of information uncertainty and unanalyzable situations. The inconsistent mediating effect of strategic decision comprehensiveness revealed in this study also has practical significance for helping entrepreneurs make correct decisions to reduce the losses caused by the pandemic.